Ultrasound-Assisted, Base-Catalyzed, Homogeneous Reaction for Ferulic Acid Production from γ-Oryzanol - Hoa Thi Truong; Manh Van Do; Long Duc Huynh; Linh Thi Nguyen; Anh Tuan Do; Thao Thanh Xuan Le; Hung Phuoc Duong; Norimichi Takenaka; Kiyoshi Imamura; Yasuaki Maeda (Journal of Chemistry, 2018)
A method for producing ferulic acid by ultrasound-assisted, homogeneous, base-catalyzed hydrolysis of γ-oryzanol was developed. Experiments were conducted using various reaction temperatures and ratios of γ-oryzanol to base catalyst in both homogeneous and heterogeneous systems. The reaction performed without ultrasound under the homogeneous conditions of potassium hydroxide/γ-oryzanol ratio (wt/wt) 20 : 1 and 75°C gave a ferulic acid yield of 83.3% in 3 h. Acceleration of the homogeneous reaction using ultrasound irradiation at 20 (horn type) and 200 kHz (planar type) was explored by evaluating the kinetic parameters. At 30°C, the ratios of ultrasonic irradiation at low (20 kHz, 50 W) and high (200 kHz, 50 W) frequencies versus those of the heating method increased by 2.0- and 1.4-fold in comparison with those at 60°C, respectively. The contribution of ultrasonic irradiation (50 W) to the hydrolysis reaction decreased with increase of temperature. However, irradiation at 20 kHz and a power of 180 W gave a 94% ferulic acid yield at 60°C in 3 h. These results indicate that the use of low frequency (horn type and high-power irradiation) enabled yields higher than 90% to be obtained.